Patterns of cation binding to the aromatic amino acid R groups in Trp, Tyr, and Phe. (February 2018) - Scherer, Shelby L.; Stewart, Amanda L.; Fortenberry, Ryan C.
Graphical abstract: Highlights: When Na+ is saturated within a system, it will dominate the cation- π interactions. Atomic cations bind stronger than the polyatomic cations to π clouds. The binding energy goes down as the partial charge increases in the atomic cations. The binding energy goes up as the partial charge increases in the polyatomic cations. Abstract: Previous joint experimental and theoretical work demonstrates that typically soluble peptides will be rendered insoluble in the presence of saturated sodium ions in aqueous solution due to disruption of cation- π interactions between Trp and Lys. The present work utilizes quantum chemical methods including density functional theory, symmetry-adapted perturbation theory, and even coupled cluster theory to determine the strengths of cation- π interactions for the aromatic R groups of Trp, Tyr, and Phe (approximated as skatole, methyl phenol, and toluene) with both alkali and alkaline-Earth atomic cations and electron-accepting R groups from Lys, Arg, and His approximated as methyl ammonium, guanidinium, and imidazolium cations. This work shows that sodium ion is still the most likely disrupter of peptide folding built upon cation- π interactions, since Trp, Tyr, and Phe all bind more strongly to sodium ion than to any of the polyatomic cations. Additionally, the atomic cation complex binding energies decrease with an increase in partial charge on the atomic cation in the complex. However, as the average partial charge increases in the interacting hydrogen atoms in the polyatomic cations, the binding energy increases. The disruption of such peptide–peptide cation- π interactions is certainly relevant for peptide design in β -sheets or β -hairpin structures, but it could also have implications for astrobiology.